2020
DOI: 10.1186/s12881-020-01176-x
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking global Stap1 expression do not manifest hypercholesterolemia

Abstract: Background Autosomal dominant familial hypercholesterolemia (ADH; MIM#143890) is one of the most common monogenic disorders characterized by elevated circulatory LDL cholesterol. Initial studies in humans with ADH identified a potential relationship with variants of the gene encoding signal transducing adaptor family member protein 1 (STAP1; MIM#604298). However, subsequent studies have been contradictory. In this study, mice lacking global Stap1 expression (Stap1−/−) were characterized under standard chow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Other genes for which notably negative results are obtained are APOB (SLP = 0.00) a known cause of familial hypercholesterolaemia, and HMGCR (SLP = -0.07), which codes for the rate-limiting enzyme in cholesterol synthesis which is the target of statins [34]. Also negative was STAP1 (SLP = -1.02), for which there were initial claims of an association with familial hypercholesterolaemia although more recent work has thrown doubt on this [35]. These three genes were also subjected to the variant category analysis and this revealed that disruptive variants in APOB were more frequent in controls (OR = 0.71 (0.60 -0.85), SLP = -3.74) but that there were much large numbers of nonsynonymous variants which overall did not show association with hyperlipidaemia, accounting for the negative result of weighted burden analysis.…”
Section: Results For Selected Genesmentioning
confidence: 99%
“…Other genes for which notably negative results are obtained are APOB (SLP = 0.00) a known cause of familial hypercholesterolaemia, and HMGCR (SLP = -0.07), which codes for the rate-limiting enzyme in cholesterol synthesis which is the target of statins [34]. Also negative was STAP1 (SLP = -1.02), for which there were initial claims of an association with familial hypercholesterolaemia although more recent work has thrown doubt on this [35]. These three genes were also subjected to the variant category analysis and this revealed that disruptive variants in APOB were more frequent in controls (OR = 0.71 (0.60 -0.85), SLP = -3.74) but that there were much large numbers of nonsynonymous variants which overall did not show association with hyperlipidaemia, accounting for the negative result of weighted burden analysis.…”
Section: Results For Selected Genesmentioning
confidence: 99%
“…The STAP1 gene was originally included in both assays due to the report by Fouchier et al (32) documenting its association with FH. This gene-disease association has since been questioned (33)(34)(35) and no potentially pathogenic variants in STAP1 were identified in this study.…”
Section: Discussionmentioning
confidence: 78%
“…The STAP1 gene was originally included in both assays due to the report by Fouchier et al (32) documenting its association with FH. This gene-disease association has since been questioned (33)(34)(35) and no potentially pathogenic variants in STAP1 were identified in this study.…”
Section: Discussionmentioning
confidence: 78%